PENDAMPINGAN PENGEMBANGAN POJOK LITERASI SEBAGAI UPAYA MENINGKATKAN BUDAYA MEMBACA ANAK DI DESA SINGODUTAN, WONOGIRI - Anita Wardani; Mustofa Mustofa; Elina Intan Apriliani; Erlina Rusdiana (Perkumpulan Pendidikan Islam Anak Usia Dini Wilayah Sumatera, 2026)
This community service program aimed to improve children’s reading culture through mentoring in the development of literacy corners in mosque environments in Singodutan Village, Wonogiri Regency. The program was implemented in two mosques that serve as locations for children’s Qur’anic learning activities (TPA) in the afternoon. The service method employed a participatory and community empowerment-based approach through preparation, implementation, and evaluation stages. The activities included providing simple bookshelves, children’s reading books, organizing comfortable reading corners, and assisting children in group reading activities. The results showed that the literacy corners successfully increased children’s enthusiasm and interest in reading. Children became more active in utilizing their free time to read before and after Qur’anic learning activities. In addition, the program created a more educational learning environment, improved children’s social interactions, and strengthened the role of mosques as centers for community education. Although several obstacles were encountered, such as limited book collections and implementation time, the program was successfully carried out with support from mosque administrators, TPA teachers, and the local community. Therefore, the development of literacy corners in mosque environments can serve as an effective strategy to foster a sustainable reading culture among children in the community.